Advanced Encryption Standard Strategy for Big Data in Cloud - G, Praveen; R, Pratheek; Mogar Y, Rahul; GB, Patil; G, Prasanna (International Journal of Computer Sciences and Engineering, 2025)
In the era of information age, due to different electronic, information & communication technology devices and process like sensors, cloud, individual archives, social networks, internet activities and enterprise data are growing exponentially. The most challenging issues are how to effectively manage these large and different type of data .Big data is one of the term named for this large and different type of data .Due to its extraordinary scale, privacy and security is one of the critical challenge of big data.Many current applications abandon data encryptions in order to reach an adoptive performance level companioning with privacy concerns. In this paper, we concentrate on privacy and propose a novel data encryption approach, which is called Dynamic Data Encryption Strategy (D2ES). Our proposed approach aims to selectively encrypt data and use privacy classification methods under timing constraints. This approach is designed to maximize the privacy protection scope by using a selective encryption strategy within the required execution time requirements